PERSEPSI DEMOKRASI INDONESIA DI ARAB SAUDI ANALISIS FRAMMING BERITA PEMILIHAN PRESIDEN INDONESIA 2019 DI SITUS ARABNEWS.COM - Mustafa Mustafa (Lembaga penelitian dan Pengabdian kepada Masyrakat, 2018)
The 2019 Presidential Election of the Republic of Indonesia, which brought Joko Widodo to power for the second time, led to various democratic events both before, or after the vote. This general election appeals to the mass media not only the media in Indonesia but also the international media. This article attempts to explain how the framing carried out by the media in the Kingdom of Saudi Arabia over the democratic process that occurred in Indonesia. To some extent, this analysis supports the claim: throughout the election, the Saudi Arabian media offered several substantive criticisms of democracy in Indonesia.